Energy Dependency and Long-Run Growth - Giacomo Novelli (Fondazione Eni Enrico Mattei (FEEM), 2022)
We investigate whether the degree of energy dependency of countries influences their macroeconomic performance in terms of long-run growth. Specifically, we study whether the impact of energy price changes on economic growth differs depending on a country's degree of energy dependency. There are two novel aspects in this paper. First, all energy commodities are considered, not only oil, and second, our work goes beyond the standard distinction between energy importing and exporting countries. We claim that energy importing and exporting countries are too heterogeneous in terms of net energy imports, energy consumption, and level of development to be clustered and analysed together. Relying on a sample clusterization in groups of countries with a similar degree of energy dependency and using a cross-sectionally augmented panel autoregressive distributed lag (CS-ARDL) approach, we show that countries with a high degree of energy dependency are associated with a negative and significant long-run energy price elasticity of GDP, while countries with a low degree experience the opposite effect, and more balanced countries are less or not significantly affected. Moreover, we contribute to the resource curse paradox showing that the energy price volatility negatively affects the long-run economic growth of countries with a low degree of energy dependency, but it does not hamper the long-run growth of other countries. We argue that the impact of energy price changes differs across countries with a different degree of energy dependency and that a balanced degree of energy dependency is preferable. Therefore, we suggest major energy importers should reduce their degree of energy dependency, while major energy exporters may differentiate their energy production, avoiding to rely only on fossil sources. Renewable sources may be a key driver to improve the management of the degree of energy dependency.
Keywords: C23; C33; O43; Q33; Q43; 330; Energy Price; Volatility; Energy Security; Economic Growth; Heterogeneous Panel; Institutions; Resource Curse